Wałbrzych meant coal: The closure of the Wałbrzych mines in the context of the socio-technical carbon lock-in - Krzywda-Starzyk, Patrycja (Wałbrzych oznaczał węgiel: likwidacja wałbrzyskich kopalń w ujęciu socjotechnicznej blokady węglowej, 2021)
During the transition of the Polish economy to a free market system in the 1990s, the coal mines in Wałbrzych were closed after nearly five centuries of extraction, which triggered over 20 years of deep socio-economic crisis in the city. This paper aimed to discuss this closure in the long-term perspective, leveraging the framework of path dependence, and in particular the socio-technical carbon lock-in. It claims that after WWII, a socio-technical lock-in occurred in Wałbrzych and the rapid closure of the mines was a consequence of its breakup resulting from the exogenous factor in the form of shock therapy. The discussion of the case of Wałbrzych contributes to the current debate on the phasing out of Poland’s coal sector slowed down by the coal lock-in.
Biblioteka Regionalisty, 2021, Nr 21, s. 62-77
Keywords: Wałbrzych; coal phase-out; socio-technical; carbon lock-in; path dependence; likwidacja przemysłu; przemysł węglowy; socjotechniczny; blokada węglowa; trajektoria rozwoju